Using Sports Science and Training Theory to Develop Elite Performance: A Case Study of a 2005 World Championship Finalist in the Women's Shot Put - Judge, L. W.; Young, M.; Wanless, E. (International Journal of Sports Science and Coaching, 2011)
Conclusions from biomechanical data can make a significant difference in the performance of athletes in the shot put if properly understood by coaches. By utilizing this scientific approach, the throws coach will be able to determine more accurate adjustments and devise training stimuli to better accommodate the athlete. The purpose of the present study was to examine the effect of a comprehensive training protocol on a performer that integrated physical capacity development and technical interventions based on a quantitative biomechanical analysis. In this case study, we have attempted to bridge the gap between the researcher and the coach in our approach to teaching and training the shot put, by integrating biomechanical analysis. This USATF Women's development shot put project is an example, in which the cooperation between sport science and coaching helped to produce a World Championship (18.58 m) berth by Elizabeth Wanless in the women's shot put in 2005.